The Social Activity of the Educator with the Family - Aliyevna, Jumayeva Malika (European Journal of Life Safety and Stability (2660-9630), 2021)
Psychological and social assistance to educators, children and parents. Family and its peculiarities. The family plays the most important role in the upbringing of the individual, compared to social institutions does Because it is in the family that individual abilities, personal, professional interests, moral norms are formed.